Biogas from Palm Oil Mill Effluent (POME): recovery to electrical energy in Sawira Biogas Plant, Muadzam Shah, Pahang / Mohammad Zulfikri Ahat - Ahat, Mohammad Zulfikri (Faculty of Plantation and Agrotechnology, 2016)
The era of palm oil mill effluent (POME) along with the production of crude palm oil has formed environmental issue for the palm oil mill industry in Malaysia due to its polluting qualities. POME with its secondary natural substance is a basis for incredible possibility for bio gas production. However, POME is ordinarily treated utilizing open ponding framework only to go along with legislature regulation without catching bio gas discharged that harmful to environment at the time it been release from mill. Biogas created from anaerobic digestion of POME can be used in gas engine to generate electric. These case study was carried out at Sawira Biogas Power Plant, Muadzam Shah, Pahang. The case study were focus on an amount of bio gas utilization, total energy production and percentage of chemical oxygen demand (COD) removal. The data was collected in four weeks observation. Total amount of bio gas utilization for four weeks is 208212 m3, total energy production is 491380 kWh and percentage COD removal is 90%.